TINDAK TUTUR ILOKUSI DALAM TRANSAKSI JUAL BELI ONLINE DI KOTA KENDARI - Nurjannah, Nurjannah; Martisa, Ela; Saerudin, Sahur; Putra, Ansor; Roza Z, Nur Rahmatiya (Seshiski: Southeast Journal of Language and Literary Studies, 2021)
Pandemic Covid 19 outbreak has been, in one side, creating social distance for sellers and buyers to the market transaction directly, but, the other side, it is also opening an online trading platform through social media. One of the trading social media platforms is Kendari Jual Beli (KJB) group in facebook, where during pandemic has increased its role in facilitating people in selling and buying goods or products. Through the process of transaction in KJB group, it is performed the communication that involved speect act. This article intends to describe illocutionary speect act in online commerce transaction in Facebook in Kendari city. It is based on the increasing prevalence of utilizing social media in online transaction in Kendari. The type of research used is qualitative research because the data in the form of words or sentences with a descriptive method. The data are taken from the conversations between the sellers and buyers at KJB. The research was conducted with the data collection stage with documentation and note-taking techniques. Furthermore, the data analysis and conclusion were carried out. The result of the study indicated that the speech act between the seller and the buyer at KJB is classified into five types of speech acts, that are directive, commissive, expressive, representatives, and declarative. In commerce transaction, buyers and sellers used the strategies. They are literal and non-literal speech acts